PENGGUNAAN METODE LIMA MENGAPA UNTUK MENGIDENTIFIKASI AKAR PENYEBAB CACAT PERMUKAAN BENDA KERJA PROSES PEMESINAN GERINDA DATAR: STUDI KASUS - Izdihar Hirzani; Arya Danutirta; Feriadi, Indra; Yudo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Surface defects of the workpiece and the emergence of sparks that suddenly enlarge during the flat grinding process cause a decrease in product quality and create unsafe working conditions. This study aims to identify the causes of surface defects of the workpiece on a flat grinding machine in the Polmanbabel advanced machining laboratory. Identification of the cause of damage using the five why analysis method. The study was preceded by defining the problem and then asking the question